Intellectual property rights protection for plant varieties in India: status, emerging issues, and challenges - P A Lakshmi Prasanna; L V Subba Rao; A S Hari Prasad; Amtul Waris; Shaik N Meera; B Nirmala; S Arun Kumar; Divya P Syamaladevi (Agricultural Economics Research Review, 2023)
Under the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) of the World Trade Organization (WTO), India recently adopted the sui generis system of intellectual property rights (IPR) protection to plant varieties . The creation and provision of IPR for plant varieties in the seed sector at the global and national levels has led to several challenges: an interplay of IPR and competition, overlapping IPRs, and an interplay of IPR and other regulations. India can draw some insights from global initiatives in providing IPR protection to plant varieties.